A data exchange solution for emergency response systems based on the EDXL-RESCUER ontology. (18th May 2019) - Salvador, Laís Do Nascimento; Barros, Rebeca; Santos, Vaninha Vieira Dos; Neto, Félix Simas De Souza; Novais, Renato Lima; Amorim, Simone Da Silva; Weber, Marian
Handling an emergency requires the coordination and cooperation of several people and systems from various agencies and organisations, including the government and society in general. A wide range of heterogeneous data is managed by different stakeholders, thus demanding solutions to support integration issues such as interoperability and ambiguity. In a previous work, we proposed an ontology for Emergency Response Systems, called EDXL-RESCUER, in the scope of the RESCUER project. In this paper, we present the usage of this ontology in a data exchange solution (DILS: Data Integration with Legacy Systems), which aims to provide semantic interoperability between Emergency Response Systems, and the evolution of EDXL-RESCUER. To evaluate the proposed solution, EDXL-RESCUER & DILS, we performed two studies: (i) simulations using two real data sources, the Police Reports from Bahia Public Safety and Security Department, Brazil; and the Canadian Disaster Database; (ii) an emergency simulation at an Industrial Park in Bahia, Brazil. The results demonstrate the potential use of the EDXL-RESCUER as a common vocabulary to support semantic interoperability between emergency response systems. We also verified the feasibility of using the DILS solution in emergency management scenarios. Besides EDXL-RESCUER & DILS, a mapping and integration of concepts related to data exchange are presented.